Developing the Ulū al-Albāb Model for Sustainable Value and Wealth Creation through Social Entrepreneurship - Mhd. Sarif, Suhaimi; Ismail, Yusof (2013)
This paper explores the development of the Ulū al-Albāb model for sustainable value and creative creation through social entrepreneurship. The Ulū al-Albāb model refers to capitalizing wisdom with a soul through the focus of seeking the Pleasure of Allah (mardhat Allah) through the obligations as servant (‘ibād al-Rahmān) and vicegerent of Allah (khālifah Allah fi al-ard). The study integrates knowledge-based view (KBV) with the Ulū al-Albāb model basis to achieve sustainable value and wealth creation for social enterprises. The primary contribution of this study is the development of model that based on the Ulū al-Albāb into KBV framework as a source to sustain intellectual contribution in terms of dynamism and ability to respond to changes. Knowledge is essential to enable social enterprises to be innovative in terms of producing new products and services to the market. The literature of strategic management and knowledge management suggests that a social enterprise with Ulū al-Albāb model is more innovative and capable of achieving sustainable competitive advantage. However, based on personal interviews with 15 informants, the study observed that social enterprises were keen to adopt Ulū al-Albāb approach due to the business model that emphasises on meeting social and economic ends simultaneously. The informants were convinced with the Ulū al-Albāb approach in sustaining competitive advantage for social enterprises in Malaysia. However, the existing business model needs a minor adjustment to fit the Ulū al-Albāb approach.